The Effect of Accounting Information System Effectiveness, Intellectual Capital, Financial Distress, and Profitability on Financial Performance - Adristi Ardelia Hanifah; Abdullah Rifqi Zahron; Maria (Yayasan Az Zukhruf Cendikia, 2026)
Purpose – This study aims to obtain empirical evidence on the Influence of Accounting Information System Effectiveness, Intellectual Capital, Financial Distress and Profitability on Financial Performance. Design/methodology/approach – This study uses a type of quantitative research. The sample in this study is 64 companies in the Health and Non-Primary Consumer Goods sectors listed on the Indonesia Stock Exchange in 2022-2024. The analysis technique used to test the hypothesis was panel data regression analysis using the Eviews 9 software. Findings – The results of the study show that the Effectiveness of the Accounting Information System has a positive effect on Financial Performance. Intellectual Capital has a positive effect on Financial Performance. And Financial Distress has a positive effect on Financial Performance. Then, the Effectiveness of Accounting Information Systems strengthens the influence of profitability on Financial Performance. Intellectual Capital strengthens the influence of profitability on Financial Performance. Financial Distress strengthens the influence of profitability on Financial Performance. Research limitations/implications – The first limitation of this research is the type of data used in this study, namely secondary data obtained from the annual report published by the company. However, the data listed is incomplete even though it is mandatory to upload financial statements every year. Furthermore, the content of the formula is confusing or incomplete, the number is not stated in the financial statements for the formula. Furthermore, this study has limitations on the sample from only 204 to 63 samples, while the rest is because the annual report data is incomplete and the company suffers losses. And finally, this study was conducted over a certain period of time, namely 2022-2024, which may not be for long-term analysis. JEL : Q56, M14, and G34